Development of Mathematics Learning Tools with Project-Based Learning for The Enhancement of Students' Social Skills and Cognitive Learning Outcomes - Masjudin, Masjudin; Kurniawan, Ade; Yuntawati, Yuntawati; Kinasih, Indira Puteri (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
Learning tools have a very important role in the learning process. Good learning tools make it easier for teachers to assist in the process of facilitating student learning. The aim of this research is to produce project-based mathematics learning tools that are valid, efficient and effective for improving students' social skills and cognitive learning outcomes. The type of research that will be used in this research is Development Research. The development model used is a development model adapted from the 4D development model (Define, Design, Develop and Disseminate). The data collection instruments used include device validation sheets, teacher and student response questionnaires, student social skills observation sheets and cognitive ability evaluation test sheets. The research results obtained: the results of device validation, the average score reached 4.2 with a very valid category; The average percentage of students' social skills scores reached 89.2% in the very good category; classical completeness reached 82% of students achieving a complete score; and teacher and student response data reached 4.2 to 93.3% which is in the very good category. Thus, it can be concluded that project-based mathematics learning tools are valid, efficient and effective for improving students' social skills and cognitive learning outcomes in statistics material.